2004
DOI: 10.1073/pnas.0406516101
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of 2-acetylaminofluorene and 2-aminofluorene in complex with T7 DNA polymerase reveal mechanisms of mutagenesis

Abstract: The carcinogen 2-acetylaminofluorene forms two major DNA adducts: N-(2-deoxyguanosin-8-yl)-2-acetylaminofluorene (dG-AAF) and its deacetylated derivative, N-(2-deoxyguanosin-8-yl)-2-aminofluorene (dG-AF). Although the dG-AAF and dG-AF adducts are distinguished only by the presence or absence of an acetyl group, they have profoundly different effects on DNA replication. dG-AAF poses a strong block to DNA synthesis and primarily induces frameshift mutations in bacteria, resulting in the loss of one or two nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(113 citation statements)
references
References 48 publications
7
106
0
Order By: Relevance
“…The newly formed dG[AF]:dC base pair, however, blocks the next template base from occupying the template preinsertion site, thereby stalling DNA synthesis. Dutta et al (53) have studied a crystal from the T7 DNA polymerase treated with ddCTP or ddATP and found sketchy electron density around the template AF-adduct. The observed disorder reflects the dynamic mobility of the AF-adduct within the active site of a crystalline polymerase and is consistent with our 19 F NMR finding, indicating that the n dC-match model adopts an S*/B*-equilibrium (Fig.…”
Section: Long-range Conformational Distortion Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The newly formed dG[AF]:dC base pair, however, blocks the next template base from occupying the template preinsertion site, thereby stalling DNA synthesis. Dutta et al (53) have studied a crystal from the T7 DNA polymerase treated with ddCTP or ddATP and found sketchy electron density around the template AF-adduct. The observed disorder reflects the dynamic mobility of the AF-adduct within the active site of a crystalline polymerase and is consistent with our 19 F NMR finding, indicating that the n dC-match model adopts an S*/B*-equilibrium (Fig.…”
Section: Long-range Conformational Distortion Effectsmentioning
confidence: 99%
“…The dramatic differences in the rates of nucleotide insertion (~10 4 -fold) observed for dG [FAF]:dC match and dG [FAF]:dA mismatch emphasize the importance of adduct-induced steric constraints in the DNA binding area, especially the minor groove interaction between the template-primer DNA and the polymerase, for determining replication fidelity (52)(53)(54)(55). Altering the adduct-induced conformational equilibria is important, but the complex features of enzyme structure and interaction with the lesion must be taken into consideration.…”
Section: Long-range Conformational Distortion Effectsmentioning
confidence: 99%
“…The amino acid sequence of ctg_CBS_polA_1019 was modeled onto structure 1 Â 9WA of T7 DNA polymerase (Dutta et al, 2004).…”
Section: Metagenomic and Phylogenetic Analysismentioning
confidence: 99%
“…Gill and Romano (20), in contrast, reported that Klenow fragment (exonuclease Ϫ ) produced a GC deletion when copying the NarI sequence with an AAF adduct at G 3 but did not provide specific evidence. Crystal structures of two replicative DNA polymerases bound to AAF-modified DNA have been solved, with Bacillus stearothermophilus pol I (45) and bacteriophage pol T7 (46). AF-adducted G appears to pair with C; in both reports the C 8 -G AAF adduct induces an anti to syn shift in the glycosidic bond, which in the case of pol T7 leads to intercalation of the AAF fluorene ring into the hydrophobic pocket of the polymerase and locks it in the "open" conformation (46).…”
mentioning
confidence: 99%